If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = (7 + -2k) * x Reorder the terms for easier multiplication: y = x(7 + -2k) y = (7 * x + -2k * x) Reorder the terms: y = (-2kx + 7x) y = (-2kx + 7x) Solving y = -2kx + 7x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = -2kx + 7x
| 15-6=9 | | 7/12t-1/4=2y-5/3 | | Q-7=3 | | 4x+(x+20)=120 | | 19+(-19)= | | -10+4(3n+10)=18 | | 4y^2+19y+12= | | -6.5t+15=-9.7t-43.8 | | 3-7y=6-8y | | -64=-8(p+1) | | X(x-48)=180 | | 12+12n=-48 | | -2x+12=0 | | 11/12t-3/4t=5/6 | | -1/7(7y+5) | | 1+6x=97 | | -2+12=0 | | x/2+14 | | 2(x+8)+3x=7+2x | | 9y-(6y+19)=6-(3y-4) | | 15-2x=3y | | 6x-8=6(x+7) | | -4y-11=4r+21 | | 0=7(a+1) | | (y^2-6y+8)/(y^2+3y-28) | | -7x-10=53 | | 5p+12=2t | | 3-2B+B+4+B=57 | | 138-x=45 | | -2x+4=-3 | | -9-3(2m-1)=-18 | | 9y+x=8 |